FROM NINGRAT TO THE BATTLEFIELD: THE HISTORY OF R.T. SUMODININGRAT OF YOGYAKARTA (1760-1812) - Mahardi, Nasta Ayundra Oktavian (Universitas Negeri Yogyakarta, 2025)
This article reviews the life of Raden Tumenggung Sumodiningrat, an important figure in Yogyakarta during the reign of Sultan Hamengku Buwono II (1792-1828), especially during the difficult period between 1808-1812. This research uses the historical method with archival and library studies to reveal Sumodiningrat's role in the Yogyakarta government. Born into a noble family, Sumodiningrat had a strong kinship with the court family and important figures such as Raden Ronggo Prawirodirjo III. He also had a special affinity with Sultan Hamengku Buwono II. This article traces Sumodiningrat's family tree, religious education by Kyai Tambi Jenggi, and career in government, starting as Wedana Jaba in 1784 to Wedana Jero in 1794. His roles included military affairs, welcoming colonial officials, and accommodating officials' complaints against the Sultan. The article also discusses Sumodiningrat's tragic end, when he died fighting to defend Yogyakarta from the British on 18-20 June 1812 (Geger Sepehi). This research aims to complete the information and data about Sumodiningrat that has not been widely reviewed in historical writings.